(untitled) (The Shivapuri Journal, 2024)
The primary responsibility of the United Nations Security Council (UNSC) is to maintain international peace and security. Since the establishment of the UN in 1948, UNSC through UNSC resolutions has pursued this aim by authorizing various peacekeeping missions. When the effectiveness of UN missions is analyzed, it has mixed responses. Some UN missions are considered very successful while some are criticized for their underperformance. The peacekeeping force has to operate in a volatile, uncertain, complex, ambiguous, and highly unpredictable environment with various limitations and constraints. The anti-UN sentiments are observed in some of the missions criticizing its ineffectiveness which has a detrimental effect on the overall credibility of the UN. In this context, the objective of this article is to highlight the challenges of contemporary peacekeeping operations and recommend ways to enhance the effectiveness of peacekeeping forces to deal with prevailing challenges. The article is qualitative and based on secondary data. The personal experience and observation of the author as a peacekeeper in various UN peacekeeping missions in different capacities is also reflected in analyzing the weaknesses and effectiveness of contemporary UN peacekeeping missions. The major findings of this article are that UN missions in Chapter VII and VIII mandate need improvement in multiple facets for the effective implementation of mission mandates like R2P and PoC. The rising anti-UN sentiments in different UN missions and increasing trend by host nations demanding the closure of contemporary UN missions further advocate revitalization in the UN peacekeeping approach.